P043 Regional differences in STI testing barriers among online testers in british columbia, canada. (14th July 2019) - Ablona, Aidan; Grennan, Troy; Salway, Travis; Shoveller, Jean; Fairley, Christopher; Krajden, Mel; Karlsson, Maja; Hiscoe, Lorena; Bannar-Martin, Sophie; Hoyano, Dee; Gomez-Ramirez, Oralia; Chang, Hsiu-Ju; et al.
Abstract : Background: GetCheckedOnline (GCO), an online sexually-transmitted infection (STI) testing service in British Columbia, launched in Vancouver, then expanded to two health regions (Island and Interior), including smaller urban and rural communities. We hypothesized that barriers to STI testing among GCO clients would be greater outside of Vancouver, due to a lower availability of existing STI services regionally. Methods: In 2015–2018, GCO clients were invited to participate in an online survey about STI testing barriers and facilitators at individual (e.g., embarrassment), healthcare provider (e.g., comfort discussing sexual health), clinic (e.g., distance, hours), and social levels (e.g., peer norms). We conducted Chi-squared, Fisher's exact, and t-tests for bivariate analyses (Vancouver vs. Interior, Vancouver vs. Island); significant results (p<0.01) are shown. Results: 583 GCO clients completed surveys: 299 (51%) Vancouver, 203 (35%) Island, and 81 (14%) Interior. Vancouver respondents included proportionately more men who have sex with men, racialized minorities, and immigrants. A higher proportion of Interior (24%) and Island respondents (18%) reported testing for the first time compared to Vancouver (8%). More Vancouver respondents reported testing through GCO for routine testing (possible other reasons: symptoms, new relationship). We found no regional differences in other barriers at individual or provider levels. Fewer Island respondents reported delaying testing in the past year due to access issues compared to Vancouver respondents (57% vs 69%), which was not explained by differences in testing history. At a social level, fewer Interior respondents reported regular STI testing as a peer norm (31% vs 58% Vancouver). Conclusion: Our findings suggest that testing barriers generally may be more universal than region-specific among users of an online STI testing service. Moreover, despite the apparently wider availability of in-person sexual health services in Vancouver, barriers in accessing these services may persist. Future socio-demographic analyses and additional research (e.g., community surveys) may help to contextualize these findings. Disclosure: No significant relationships.